2020
DOI: 10.1002/bdr2.1854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of structural birth defects among infants with Down syndrome, 2013–2017: A US population‐based study

Abstract: BackgroundDown syndrome is the most common chromosomal disorder at birth and is often accompanied by structural birth defects. Current data on major structural defects in this population are limited.MethodsStates and territorial population‐based surveillance programs submitted data on identified cases of Down syndrome and identified structural birth defects during 2013–2017. We estimated prevalence by program type and maternal and infant characteristics. Among programs with active case ascertainment, we estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…We limited cases to ≥20 weeks gestation (or 350 g birthweight where gestational age was missing) to allow for diagnosis of co‐occurring congenital anomalies. To examine co‐occurring congenital anomalies, we followed the methods described in Heinke et al (2021). However, due to the small cell sizes resulting from stratification by maternal race/ethnicity, we limited this analysis to major and minor congenital anomalies by organ systems and four selected cardiovascular birth defects commonly associated with DS: atrial septal defect (ASD), atrioventricular septal defect (AVSD), tetralogy of Fallot (TOF), and ventricular septal defect (VSD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We limited cases to ≥20 weeks gestation (or 350 g birthweight where gestational age was missing) to allow for diagnosis of co‐occurring congenital anomalies. To examine co‐occurring congenital anomalies, we followed the methods described in Heinke et al (2021). However, due to the small cell sizes resulting from stratification by maternal race/ethnicity, we limited this analysis to major and minor congenital anomalies by organ systems and four selected cardiovascular birth defects commonly associated with DS: atrial septal defect (ASD), atrioventricular septal defect (AVSD), tetralogy of Fallot (TOF), and ventricular septal defect (VSD).…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have indicated that the prevalence of DS varies by race and ethnicity within the United States. For example, the highest prevalence is among children born to Hispanic mothers (15.4–16.6 per 10,000 live births), while the prevalence among children born to non‐Hispanic Black and non‐Hispanic Asian or Pacific Islander mothers is lower (10.2–10.9 and 10.8–11.6 per 10,000 live births, respectively) (Heinke et al, 2021; Mai et al, 2019). However, patterns of co‐occurring congenital anomalies by race and ethnicity are only beginning to be described (Freeman et al, 2008), which limits our understanding of disparities among individuals with DS.…”
Section: Introductionmentioning
confidence: 99%
“…Trisomy 21 is the most common chromosomal disorder, approximately 1 of 800 births worldwide [18], with CHD found in 44 %-66 % of these infants [18,19]. The highest rate of trisomy 21 in this study was in patients with AVSD/ECD (31.1 %), followed by PDA, VSD, PTA, TOF, Ebstein, and ASD.…”
Section: Trisomy 21mentioning
confidence: 51%
“…The occurrence of SUA becomes more frequent when the mothers considered for the study suffer from medical and pregnancy complications. Such maternal health problems include preexisting diabetes, high blood pressure, placental abnormalities, and epileptic episodes [2,17,18] .If the mother undergoes frequent administration of levothyroxine or phenytoin, is dependent on other drugs, has an irregular pattern of conception that may be seasonal, etc also puts the fetus at risk for SUA [10,11,12,19].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The prevalence of SUA varies from population to population examined and the timeline of testing, which is found to be from 0.2 percent in newborns to 11% in high-risk fetuses at 11-14 weeks of gestation. [9, 6,10,11].…”
mentioning
confidence: 99%